Refining the maritime boundary delimitation approach through decisions of international courts: towards predictability and certainty - Hamid, Abdul Ghafur@Khin Maung Sein (2017)
According to Articles 74(1) and 83(1) of the United Nations Convention on the Law of the Sea (UNCLOS) 1982, the maritime boundary delimitation is to be affected by agreement in accordance with international law in order to achieve equitable solution. The rule is inherently vague, controversial and allows the courts unprecedented discretionary power to determine how an equitable solution could be achieved. This watered-down and compromised formula of the UNCLOS 1982 is due to lack of consensus among negotiating States at the time of drafting the convention. The present paper makes an analytical study of the decisions of the International Court of Justice and the International Tribunal for the Law of the Sea on this issue in order to examine whether a consistent maritime boundary delimitation approach has been established through the jurisprudence of the courts. The paper traces the evolving trend of judicial precedents from the equitable principles of the Norther Sea Continental Shelf cases to the two -stage approach initiated in Jan Mayen Case and followed in many other cases, to the three-stage approach of the Black Sea and the more recent cases of the Bay of Bengal and the Columbia-Nicaragua. The paper concludes that while over the past three decades a clearer approach to maritime delimitation has emerged through the decisions of the international courts, there are still subjectivity and uncertainty in the choice of basepoints prior to constructing the provisional delimitation line and in the context of the practical application of the established delimitation approach.